Effects of microsite variation on growth and adaptive traits in a beech provenance trial - D. Gömöry; L. Paule; E. Gömöryová (Journal of Forest Science, 2011)
ABSTRACT: The effects of the within-trial spatial variation of environmental factors on phenotypic traits were studied in the Slovak plot of the international beech provenance trial coordinated by BFH Grosshansdorf with 32 provenances, established under a randomized complete block design with three adjacent blocks. Five indicators of soil properties (soil moisture, bulk density and pH) and microclimate (average daily temperature and temperature amplitude) were assessed at 96 points distributed over a 10 × 10 m grid and their values for the positions of individual trees were estimated by ordinary point kriging. The evaluation of phenotypic variation (height, diameter, Julian days of spring flushing and autumn leaf discoloration, vegetation period length, late frost damage) using a common two-way analysis of variance showed a significant provenance × block interaction effect indicating the heterogeneity of blocks. Analysis of covariance using single-tree kriging estimates of environmental variables as covariates showed that in addition to provenance, all phenotypic traits were significantly affected by microsite, especially by temperature fluctuation. Employing methods incorporating the spatial component in the evaluation of tree breeding field experiments is advocated.